Reconciling cultural practices and progress: childbirth in Dove, Ghana. Issue 4 (18th May 2016) - Arku, Frank S.; Arku, Cynthia
ABSTRACT: Women are forbidden from giving birth within the community in Dove, Ghana because it is against their culture. Such cultural practice is scarce in contemporary societies so studies on the impact of the practice are currently limited in development literature. This article uses key informant interviews and focus group discussion guides to gather data. Findings reveal that the Chief, the Queenmother, and other community members maintain that the practice is not negatively affecting the socio-economic development of Dove as they have strategies to mitigate the practice.